AB0674 Axial Spondyloarthrits – What Target for Treatment?. (10th June 2014) - Hayward, R.; Harris, E.C.; Keat, A.
Abstract : Background: The concept "treat to target (T2T)" is a guide to optimising treatment outcomes in rheumatoid arthritis. T2T is also advocated in axial spondyloarthritis (axSpA) 1 but potential targets are unclear and few treatments are available. Of the potential treatment targets ASDAS and the patient reported outcome measures (PROMs), BASDAI, BASFI and BAS-G are the most readily available measures in clinical practice. We have reviewed PROM and ASDAS data from patients with axSpA attending a SpA clinic in the UK to assess their potential as targets for treatment. Objectives: To assess whether specific levels of BASDAI, BASFI, BAS-G or ASDAS are achieved by sufficient proportions of patients with axial SpA in "real life" clinical practice to justify potential target status. Methods: Patients with axSpA were asked to complete BASDAI, BASFI, and BAS-G as per routine clinical practice. ASDAS was calculated where timely measures of CRP or ESR were available. The "latest" score set was used. All patients fulfilled ASAS criteria for axSpA or modified New York criteria for AS and completed the BASDAI but fewer completed the other PROMs. All patients were on stable treatment regimes, receiving "normal care"; the full range of treatments for axSpA were available to all patients, according to National clinical guidelines. Results: Data from 130 (96 male) patients receiving non-biologic and 90 (76 male) receiving biologic treatment are reported. The mean scores for BASDAI, BASFI and BAS-G, the range of scores and the proportion of scores below 2, 4, 6 and 8 are shown for male and female patients receiving non-biologic and biologic treatment in table 1 . Mean scores below 4 were achieved only by males receiving biologics (BASDAI) and women receiving biologics (BASFI and BAS-G). Scores amongst biologic patients were lower than the non-biologic group but only at the <8 level did more than 80% of patients achieve that target. 39.6 and 38.2% of men and women not receiving biologic treatment achieved a BASDAI of <4. ASDAS was calculated in 59 (45 male) non-biologic and 44 (36 male) biologic patients. Scores of <1.3, 1.3 <2.1, 2.1 - 3.5 and >3.5 were obtained in 13.6, 16.9, 49.2, and 20.3% non-biologic and 31.8, 25.0, 34.1, and 9.1% biologic patients. 30.5% of non-biologic and 56.8% of biologic patients had ASDAS scores in the "inactive" or "low disease activity" ranges. Conclusions: It is clear that in clinical practice: - The range of PROM outcomes associated with routine treatment of axSpA is wide whether or not biologic agents are used. - 30.5% of non-biologic and 56.8% of biologic patients achieved ASDAS low disease activity or remission. - The benefits of stepping up treatment by maximising NSAID intake, earlier use of biologic agents or switching biologic agent need to be studied. - Measures of social and work function may provide better treatment targets. References: Smolen J et al. Ann Rheum Dis 2014; 73:6-16. Disclosure of Interest: R. Hayward Grant/research support: Pfizer, E. Harris Speakers bureau: Pfizer, UCB, Abbvie, MSD, A. Keat Paid instructor for: Pfizer, UCB, Abbvie, MSD, Speakers bureau: Pfizer, UCB, Abbvie, MSD DOI: 10.1136/annrheumdis-2014-eular.2201